TINJAUAN EKONOMI PROVINSI RIAU - Wawan Hermawan (Bina Ekonomi, 2008)
Riau Province is one of the most faster income per capita growth in sumatera lslands. The economic base of economic structure in Riau Province is Forestry sector. This leading sector improve government income through Local tax income. This phenomenon", contradiction with inequality, unemployment,  and poverty  rate where in theoretically  this indicators has negatif sign correlated with growth with  income per capita, the reason of this fact because  the income GDP  from basis  sector are centralized  to capital  owner.